Small area statistics and quality management –the Polish perspective - Kordos, Jan (Silesian Statistical Review, 2018)
The author begins with a discussion of the main factors affecting the efficiency of decision-making, and in particular the quality of the information used, the models applied and the knowledge of decision-makers in the field of the implementation. First, we considered the acronym GIGO (“garbage in garbage out”) used in computer science, expressing the impact of the relationship between the quality of the information used in the model, and their outcome, and then the Box aphorism about the usefulness of models (“All models are wrong but some are useful”). Particular attention is paid to the statistics of small areas, discussing their source, size, and mainly their quality, giving the current definition of data quality. Next the author provided the development of estimation methods for small areas, apart from mathematical formulas and limited to the presentation of some flowcharts. The author then discusses the role of small area statistics in quality management, focusing on the evaluation of their quality, which is of particular importance when making decisions. The paper is prepared from the Polish perspective, referring mainly to Polish statisticians and some relevant publications in English
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2018, Nr 16, s. 37-54
Keywords: efficiency of decision-making; the quality of the information; model; the acronym GIGO; statistics of small areas; quality management; sources of statistical data